MAKNA TEKS PADA LAGU OUD BATAVIA OLEH GRUP MUSIK KRONTJONG TOEGOE - Khoirun, Muhamad Sandy (SELONDING, 2025)
This study examines the song Oud Batavia by the music group Krontjong Toegoe, focusing on its creation process, musical characteristics, and its social, cultural, emotional, and educational functions. The method used is the diachronic historical method, and data collection obtained from literature sources and other sources in physical and digital form as well as direct interviews with Kerontjong Toegoe actors to trace the meaning of the song text which has undergone changes and developments along with the underlying social, cultural and historical dynamics.The analysis is based on Jean-Jacques Nattiez’s theory of musical semiotics, where the textual aspect is analyzed using semiotics to reveal the meaning of the song's lyrics. The findings show that, first, the creation of Oud Batavia was influenced by the social and cultural life of Batavia in the early to mid-20th century. Second, the musical form of this song combines elements of traditional keroncong music with European cultural influences, featuring a musical structure that blends the keroncong style with the European Waltz style. Third, the functions of Oud Batavia include cultural preservation, a medium of communication, a tool for learning history, music and arts education, and the instillation of cultural values.